Math, asked by bm291885, 8 months ago

Find the value of k for which the quadratic equation (k - 2)x^2 (2k - 3)x +(5k - 6)=0
has real roots​

Answers

Answered by AlluringNightingale
5

Answer :

k € [7/6 , 3/2]

Note:

★ The possible values of the variable which satisfy the equation are called its roots or solutions .

★ A quadratic equation can have atmost two roots .

★ The general form of a quadratic equation is given as ; ax² + bx + c = 0

★ The discriminant , D of the quadratic equation ax² + bx + c = 0 is given by ;

D = b² - 4ac

★ If D = 0 , then the roots are real and equal .

★ If D > 0 , then the roots are real and distinct .

★ If D < 0 , then the roots are unreal (imaginary) .

Solution :

Here ,

The given quadratic equation is ;

(k - 2)x² + (2k - 3)x + (5k - 6) = 0

Comparing the given quadratic equation with the general quadratic equation ax² + bx + c = 0 , we have ;

a = k - 2

b = 2k - 3

c = 5k - 6

Now ,

The discriminant D of the given quadratic equation will be given as ;

=> D = b² - 4ac

=> D = (2k - 3)² - 4•(2k - 3)•(5k - 6)

=> D = (2k - 3)² - 4(10k² - 12k - 15k + 18)

=> D = 4k² - 12k + 9 - 4(10k² - 27k + 18)

=> D = 4k² - 12k + 9 - 40k² + 108k - 72

=> D = -36k² + 96k - 63

Also ,

We know that , for real roots of a quadratic equation , its discriminant must be equal to or greater than zero .

Thus ,

=> D ≥ 0

=> -36k² + 96k - 63 ≥ 0

=> -3(12k² - 32k + 21) ≥ 0

=> 12k² - 32k + 21 ≤ 0

=> 12k² - 14k - 18k + 21 ≤ 0

=> 2k(6k - 7) - 3(6k - 7) ≤ 0

=> (6k - 7)(2k - 3) ≤ 0

=> k € [7/6 , 3/2]

Hence ,

k € [7/6 , 3/2]

Attachments:
Similar questions